Role of work-family enrichment in improving job satisfaction - Ng, Swee Fung; Ahmad, Aminah; Omar, Zoharah (Science Publications, 2014)
The role of work-family enrichment in improving job satisfaction has been given little attention. In this study a mediation model was tested which includes work-family enrichment as the mediator, job characteristics (job autonomy and job involvement) as antecedent factors and job satisfaction as the outcome. Data were gathered from 280 public secondary school teachers in Malaysia using self-administered questionnaires. Work-family enrichment partially mediated the relationships between job characteristics and job satisfaction. The results contribute towards understanding how work-family enrichment could help improve job satisfaction.